Key factors of venture capital investments in Europe - Leppälä, Eeli (2024)
The purpose of this master’s thesis is to identify key factors that influence venture capital investments in Europe. European venture capital investments have increased significantly especially between the years 2016-2021. However, current literature has mainly focused on the turn of the 2000s and hence does not consider the period of rapid growth.